2018
DOI: 10.18203/2319-2003.ijbcp20183031
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization pattern of antiepileptic agents among pediatric epilepsy at tertiary care teaching hospital of Gujarat: a cross sectional study

Abstract: Background: Epilepsy is one of the most common neurological disorders characterized by recurrent episodic paroxysmal involuntary clinical events associated with abnormal electrical activity from the neurons. Without the knowledge of how drugs are being prescribed and used, it is difficult to initiate discussion on rationale drug use and to suggest measures to change prescribing habits for the better management. Present study was performed with an aim to study the utilization pattern of anti-epileptic drugs (AE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…One study had contrast results as compared to the study done by Bhatt et al, in Gujarat and Krutika et al, (12). We observed that 27.4% were in the age group between 11-15 years and correlating results with the study by Dave et al, (13). In our study 64.8% were from urban background.…”
Section: Discussionsupporting
confidence: 92%
“…One study had contrast results as compared to the study done by Bhatt et al, in Gujarat and Krutika et al, (12). We observed that 27.4% were in the age group between 11-15 years and correlating results with the study by Dave et al, (13). In our study 64.8% were from urban background.…”
Section: Discussionsupporting
confidence: 92%
“…Thesefindings were in consonance with other studies done by Dave et al, which observed that 86% of patients were immunized[15]. Certain diseases such as measles, diphtheria, pertussis, tetanus, etc., cause brain damage as well as febrile episodes, which may lead to febrile convulsions.…”
supporting
confidence: 92%
“…The seizure status was considered controlled if the patient had not experienced any seizure attacks in the past year, and not controlled if the patient experienced one or more seizure attacks in the last one year follow up period [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%